PENTINGNYA TEKNIK GOOD LOBBY DALAM KOMUNIKASI GOOD GOVERNANCE - Gayos Alfajri (Governance, 2024)
In Good Governance Practices, lobbying is a part of communication that plays an important role for government administrators to reach mutual agreements in government activities. Good and effective lobbying can affect the smooth running of government programmes because it can help in creating relationships and cooperation between interest groups in a government area. The purpose of this research is to analyse how good lobbying is applied in good governance practices in order to successfully undergo good lobbying for every government program activity. This research uses the library research method, which is a method that uses secondary data sources by finding references through journals, books, literature, notes, and various other documents related to the problem to be solved. The results of the study state that the success of good lobbying in government practice. Successful lobbying and negotiation depends on skills in mastering verbal and non-verbal communication, the ability to analyse and solve problems, careful preparation, active listening, smart in controlling emotions, commitment, and knowing the negotiation style of others.